Improvements in strength and functional performance after Kinesio taping in semi-professional male soccer players with and without functional ankle instability. (December 2019) - Fereydounnia, Sara; Shadmehr, Azadeh; Attarbashi Moghadam, Behrouz; Talebian Moghadam, Saeed; Mir, Seyed Mohsen; Salemi, Saba; Pourkazemi, Fereshteh
Highlights: The application of Kinesio taping improved the strength of the hip abductor and ankle evertor muscles in semi-professional male soccer players. The performance in side hope test and star excursion balance test in anterior and posterolateral directions improved after the application of Kinesio taping in semi-professional male soccer players. No differences between two methods of Kinesio taping over (1) peroneus longus, (2) gluteus medius and peroneus longus muscle were found. Abstract: Objective: The objectives of this study were to compare the immediate effects of two methods of Kinesio taping on muscle strength, functional performance, and balance in athletes with and without functional ankle instability (FAI). Methods: The present study investigated the effects of distal taping (muscle application over peroneus longus) and proximal- distal taping (muscle application over gluteus medius and peroneus longus) on the strength of evertor and hip abductor muscles, side hop test, figure of 8 hop test, and star excursion balance test in semi-professional male soccer players with and without FAI (n = 15 in each group). A Multifactorial repeated measure ANOVA was used for comparison. Results: There were significant differences for factor effect in all outcome measures (P < 0.05), except for the figure of 8 hop test. No significant differences for group effects and group by factor interaction effects (P > 0.05) was observed except for the side hop test. Conclusion: Kinesio taping had immediate effects on improving strength, performance and balance. However, there were no differences on the method of application. Clinicians can consider the application Kinesio taping during the rehabilitation process of athletes with FAI, to improve balance and strength. The long-term impacts of taping on the functional, balance and strength measures should be investigated in future studies.